Promoting high-order thinking skills through problem-based learning: design and implementation - Mustakim, Siti Salina; Sulaiman, Tajularipin; Lei, Xiaoyi; Zou, Yuxue (Human Resources Management Academic Research Society (HRMARS), 2024)
PBL (Problem-Based Learning) has significant importance in enhancing critical thinking, creative thinking, problem-solving, and promoting HOTS (Higher-Order Thinking Skills) and 21st-century skills. However, while there has been a lot of research on PBL, most of it has focused on the fields of medicine and physics, with few and often disorganized studies in the field of education, especially those using literature review methods. The purposes of this study are: (1) to classify and compare case studies on "Problem-Based Learning" and extract relevant conclusions, and (2) to summarize universally applicable "PBL" teaching strategies and provide recommendations. This review focuses on the specific implementation procedures of PBL teaching strategies over the past decade. The study finds that in teaching contexts such as group collaborative learning, role-playing, and STEAM (Science, Technology, Engineering, Arts, and Mathematics), problem-based teaching can effectively promote the development of students' critical thinking, creativity, problem-solving abilities, and other higher-order thinking skills. This research enriches the theoretical foundation of PBL operational procedures and provides important references for teaching practice.